Regulatory T cells in canine cancer - Burton, Jenna Hart, author; Biller, Barbara J., advisor; Avery, Anne C., committee member; Dow, Steven W., committee member; Thamm, Douglas H., committee member (Colorado State University. Libraries, 2011)
Numbers of regulatory T cells (Treg) are increased in some human malignancies and are often negatively correlated with patient disease-free interval and survival. Canine Treg have previously been identified in healthy and cancer-bearing dogs and have found to be increased in the blood of dogs with some types of cancer. Moreover, some preliminary research indicates that increased numbers of Treg and decreased numbers of CD8+ T cells in the blood of dogs with osteosarcoma (OSA) are associated with decreased survival. The aim of this project was to examine Treg distributions in dogs with cancer compared to normal dogs and to determine any association between Treg numbers and patient outcome. Additionally, we sought to determine if treatment with daily low-dose (metronomic) chemotherapy would decrease Treg in dogs with cancer. Pre-treatment Treg populations in blood, tumors, and lymph nodes of dogs with OSA were assessed and compared with Treg in blood and lymph nodes of a healthy, control population of dogs. No significant changes in Treg numbers in the blood or lymph nodes of the OSA-bearing dogs compared to the control population were identified. The dogs with OSA with treated with amputation of the affected limb followed by adjunctive chemotherapy. Treg numbers in the blood or tumor were not associated with outcome but an elevated ratio of CD8+ T cells to Treg in the tumor was associated with a prolonged disease-free interval and increased survival. These findings suggest that changes in number of Treg and effector T cell subset may provide prognostic information for canine OSA. In mice and humans with advanced cancer, the administration of metronomic (daily low dose) cyclophosphamide (CYC) selectively decreases circulating Treg numbers and inhibits their function. Protocols containing metronomic CYC likely have anti-tumor properties in dogs as well. Despite wide use of metronomic CYC in veterinary medicine, its effects on canine Treg have not previously been reported. Dogs with soft tissue sarcoma (STS) were administered CYC at 12.5 mg/m2 or 15 mg/m2 orally once daily for 28 days. Whole blood samples and tumor biopsies were obtained on days 0, 14, and 28 to assess changes in T lymphocyte subsets, circulating endothelial cells, and tumor microvessel density (MVD). Administration of CYC at 12.5 mg/m2/day significantly decreased the number of Treg from day 0 to 28, but there was no change in the percentage of Treg or tumor MVD. In dogs that received CYC at 15.0 mg/m2/day, both the number and percent of Treg as well as tumor MVD were significantly decreased over 28 days. These findings suggest that metronomic dosing of CYC may have immunomodulatory and antiangiogenic effects in dogs with cancer. Taken together the work described in this thesis support the theory that Treg are altered in dogs with cancer and that these changes may have prognostic value. Additionally, Treg can be decreased in dogs with cancer though administration of metronomic doses of CYC; the therapeutic benefit of Treg depletion has yet to be evaluated in cancer bearing dogs.
Keywords: osteosarcoma; metronomic chemotherapy; soft tissue sarcoma; dog; low dose chemotherapy